Perceived discrimination, self-esteem and well being of disabled adolescents in SPED-ISEC, Iloilo City. - Hermusura, Eden J.; Asong, Fritz Gerald F. (2010.)
This study examined the perceived discrimination, level of self-esteem, and psychological well-being of students who are disabled in whom are in their adolescent years enrolled in SPED-ISEC, Iloilo City., Six (6) and four (4) females with ages ranging from 13-19 years old were the participants in the study. A likert-type scale formulated by the researchers were used to identify the areas of perceived discrimination of the respondents. Two standardized scales were utilized to rate the level of self-esteem, and the levels of psychological well-being of the respondents. It was found out that the disabled adolescents in SPED-ISEC, Iloilo City generally have low perceived discrimination, slightly high level of self-esteem and have positive psychological well-being.
Research Project (Undergraduate, Bachelor of Arts in Psychology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Disabled Adolescents